Retrofit water systems the SHARPS way - Alwi, Sharifah Rafidah Wan; Manan, Zainuddin A.; Samingin, Mohd. Hisham; Misran, Norrazi (American Institute of Chemical Engineers, 2006)
The use of Systematic Hierarchial Approach for Resilient Process screening (SHARPS) technique has provided quick and systematic isolation and affordable water management options prior to design of minimum-water-network (MWN). Water pinch analysis (WPA) has been widely used throughout the chemical and other industries as a tool for the design of maximum-water-recovery (MWR) networks. An important tool for water management is the water management hierarchy, which guides the prioritization of process changes qualitatively and quantitatively. It is observed that implementation of each process change option will yield new pinch points and MWR targets. By applying the SHARPS methodology in accordance with the water management hierarchy, it is possible to identify which schemes should be partially applied or completely eliminated to satisfy a desired payback period, allowing the designer to estimate the maximum potential annual savings.